Free Will & Action Historical and Contemporary Perspectives (Historical-Analytical Studies on Nature, Mind and Action,, 2018)
This book consists of eleven new essays that provide new insights into classical and contemporary issues surrounding free will and human agency. They investigate topics such as the nature of practical knowledge and its role in intentional action; mental content and explanations of action; recent arguments for libertarianism; the situationist challenge to free will; freedom and a theory of narrative configuration; the moral responsibility of the psychopath; and free will and the indeterminism of quantum mechanics. Also tackling some historical precursors of contemporary debates, taken together these essays demonstrate the need for an approach that recognizes the multifaceted nature of free will. This book provides essential reading for anyone interested in the current scholarship on free will.